Metabolic and chemical studies on N-(4-chlorobenzyl)-N '-benzoylhydrazine - (:unkn) unknown (ELSEVIER SCIENCE SA, 2000)
The in vitro hepatic microsomal metabolism of N-(4-chlorobenzyl)-N'-benzoylhydrazine (CBBAH), a model compound representing N-alkyl substituted hydrazides, was studied using hepatic washed rat microsomal preparations fortified with NADPH to identify the possible N-oxidative, N-dealkylated and hydrolytic metabolites. CBBAH and its potential metabolites were prepared, characterized using spectroscopic techniques and then separated using a reversed phase HPLC system with UV detection at 254 nm. CBBAH was chemically converted to the corresponding hydrazone by m-chloroperbenzoic acid (m-CPBA) oxidation. CBBAH was incubated with rat microsomal preparations in the presence of NADPH, extracted into dichloromethane and evaporated finally under nitrogen. The TLC and HPLC results from the metabolic experiments showed that CBBAH produced the corresponding hydrolytic and N-dealkylated metabolites together with the corresponding hydrazone. (C) 2000 Published by Elsevier Science S.A. All rights reserved.
Keywords: N-alkyl hydrazide; hydrazone formation; secondary amines; in vitro metabolism; AGENTS